(untitled) (Indian Journal of Chemistry (IJC), 2023)
Chemical reduction of organic azides is a commonly accepted route in synthetic organic chemistry to prepare amino compounds. Researchers and scientists are interested in choosing greener pathways in the course of the synthesis of organic molecules. In the present work we report the synthesis of benzene sulphonamide by the electrochemical reduction of benzene sulphonyl azide using platinum electrodes. Influence of current density and voltage, effect of electrolytes, effect of solvents and effect of substrate concentration on the yield of the product have been studied. The reaction is more feasible in the presence of sodium ascorbate (in 1:1 methanol-water) which acts as both supporting electrolyte and electron transferring agent in the electrochemical process.